The IMPLEMENTATION OF THE REGIONAL FINANCIAL ACCOUNTING SYSTEM, PRESENTATION OF FINANCIAL STATEMENTS, ACCESSIBILITY, AND INTERNAL CONTROL SYSTEM HAVE AN EFFECT ON THE ACCOUNTABILITY OF REGIONAL FINANCIAL MANAGEMENT - Poppy Indrihastuti; Sri Indah; Grestiana Bili (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2022)
This study aims to examine the effect of regional financial accounting systems, accessibility of financial reports and internal control on regional financial management accountability. This research is a quantitative research. The population in this study were all parts involved in the management of regional finances in urban villages in the city of Malang. The sampling technique used is simple random sampling. The data collection technique used in this study is primary data in the form of questionnaires distributed to respondents. The analytical method used is multiple regression analysis with SPSS version 26. Based on the results of the study, it shows that the regional financial accounting system, accessibility of financial statements, and internal control have a tcount > ttable (121.950> 2.69 with a significant value of 0.0000<0.05 (?=5%). Based on the results of the study, it can be concluded that the variables X1, X2, X3, and X4 together have an effect on Y, a significant positive effect on the accountability of regional financial management.